The Pengaruh Lingkungan Kerja dan Kepemimpinan Terhadap Kinerja Pegawai Dinas Pariwisata Kabupaten Labuhanbatu Selatan - Mulkan Ritonga; Rahma Muti'ah; Muhammad Alam Warda Ritonga (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
Performance is one of the benchmarks in assessing the performance of an organization, both government organizations and private organizations. Performance measurement can affect various factors, both factors originating from within the organization and factors from outside the organization. This study aims to determine the effect of the work environment and leadership on employee performance. The population in this study were all employees at the South Labuhanbatu Regency Tourism Office using the census technique as a sampling technique. The research method chosen is associative descriptive quantitative research. This type of research aims to see and explain the influence between variables in the study using a questionnaire technique as a data collection instrument. The results showed that the work environment and leadership had a positive and significant effect on employee performance, both partially and simultaneously. Environment and leadership variables contributed 67.40% to employee performance at the South Labuhanbatu Regency Tourism Office, while the remaining 32.60 % influenced by other factors not examined in this study.